Driving mechanism of consumer migration behavior under the COVID-19 pandemic - Wang, Dong; Chen, Weishan; Zheng, Xiarou; Wang, Xuetong (Frontiers in Public Health, 2023)
China is now in the post-period of COVID-19 epidemic prevention and control. While facing normalized epidemic prevention and control, consumers’ behavioral intention and decision-making will still be influenced by the epidemic’s development and the implementation of specific epidemic prevention measures in the medium to long term. With the impact of external epidemic prevention environment and measures, consumers’ channel behavior has changed. How to better promote channel integration by adopting consumers’ channel migration behavior is important for channel coordination strategies. This paper takes fresh product retailing under normal epidemic prevention and control as an example and examines the change in channel migration behavior. Based on the value-based adoption model (VAM), this paper discusses the influence of channel characteristics and channel switching costs on channel migration intention, the mediating effect of perceived value between various influencing factors and channel migration intention, and the moderating effect of channel switching cost on perceived value and channel migration intention. The results show that under normal epidemic prevention and control, the influencing factors in the VAM model have a significant impact on channel migration intention; perceived value plays a mediating role between various influencing factors and channel migration intention.